2020
DOI: 10.1111/jocn.15579
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve human papillomavirus vaccination rates among adolescents in family practice settings in the United States: A systematic review

Abstract: Aims and Objectives To explore the interventions aimed at increasing human papillomavirus (HPV) vaccination rates among adolescents in family practice settings. Background HPV is the most common sexually transmitted disease in the United States, and the cause of thousands of anogenital and oropharyngeal cancers annually. Although HPV infection can be prevented with recommended vaccination during adolescence, national HPV vaccine rates remain low. Design Systematic review. Methods Four databases (MEDLINE, CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(42 citation statements)
references
References 32 publications
0
38
0
3
Order By: Relevance
“…21,23,[25][26][27][28] Most of the included primary studies in the systematic reviews were conducted in the USA. [20][21][22][23][24][25][26][27][28][29] Other countries that were represented were Australia (n=5), 21,[23][24][25]28 the UK, (n=3) 20,23,24 Sweden (n=3), 20,23,24 India (n=2), 24,27 Canada (n=1), 28 China (n=1), 27 Hong Kong (n=2), 23,24 Hungary (n=1), 23 Ireland (n=1), 24 Singapore (n=1), 23 Tanzania (n=1), 20 and Taiwan (n=1). 23 Two reviews only included studies from the USA.…”
Section: Characteristics Of Included Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…21,23,[25][26][27][28] Most of the included primary studies in the systematic reviews were conducted in the USA. [20][21][22][23][24][25][26][27][28][29] Other countries that were represented were Australia (n=5), 21,[23][24][25]28 the UK, (n=3) 20,23,24 Sweden (n=3), 20,23,24 India (n=2), 24,27 Canada (n=1), 28 China (n=1), 27 Hong Kong (n=2), 23,24 Hungary (n=1), 23 Ireland (n=1), 24 Singapore (n=1), 23 Tanzania (n=1), 20 and Taiwan (n=1). 23 Two reviews only included studies from the USA.…”
Section: Characteristics Of Included Systematic Reviewsmentioning
confidence: 99%
“…23 Two reviews only included studies from the USA. 22,29 The total number of participants across all ten systematic reviews was 451,132 and the number of participants in each systematic review ranged from 2625 21 to 276,205 22 with all reviews, except one 22 including studies with small sample sizes of less than 200 participants. Five systematic reviews did not report the ethnicity of participants 20,21,23,27,28 and in one further systematic review, 28 of the 30 included studies did not report on ethnicity.…”
Section: Characteristics Of Included Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…HIYA! was designed based on current evidence that multimodal approaches involving measures pre-, during, and post-visit are the most effective method to increase HPV vaccination rates in family practice (Eisenhauer et al, 2020). HIYA!…”
Section: Hiya! Interventionmentioning
confidence: 99%
“…A pooled analysis of five randomized controlled trials suggested that reminder systems significantly increased HPV vaccination rates (Dempsey et al, 2019;Eisenhauer et al, 2020;Henrikson et al, 2018;Rand et al, 2017;Szilagyi et al, 2015Szilagyi et al, , 2020. Reminder systems included phone calls, text messages, emails and postcards.…”
Section: Re Vie W Of Liter Aturementioning
confidence: 99%